COMPARATIVE GASTRIC ULCEROGENIC EFFECTS OF NAPROXIN, FENOPROFEN AND RECTIFIED SPIRIT IN ALBINO RAT - Daraz, Umar; Janjua, Muhammad Zahoor (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: A study of comparative ulcerogenicity of naproxen, fenoprofen and rectified spirit was conducted under dissecting as well as laboratory microscope. Different parameters of mucus barrier disruption were studied in detail and a statistical comparison was made between the three drugs used. It was found that under dissecting microscope the difference was non-significant but under light microscope naproxen was maximally ulcerogenic followed by rectified spirit and fenoprofen was least ulcerogenic.